2013
DOI: 10.5222/terh.2013.72626
|View full text |Cite
|
Sign up to set email alerts
|

The Rate Of Development Postnatal Obstructive Uropathy In Fetal Hydronephrosis

Abstract: ÖZETAmaç: Gebelikte ultrasonografinin yaygın kullanımı ve doğum öncesi hidronefrozun artan sıklıkta tanımlanmasıyla, bu hastaların doğum sonrasında izlemin önemi giderek artmaktadır. Bu çalışmada doğmalık üriner sistem malformasyonlarının önemli bir bölümünü oluşturan obstrüktif üropatilerin tedavisinde erken tanının ve obstrüktif üropatili çocukların tanısal sü-recinde kullanılan radyolojik ve sintigrafik tetkiklerin önemini araştırmayı amaçladık.Gereç ve Yöntem: Doğum öncesinde yapılan ultrasonografi ile fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…[1] While in most cases, urological abnormalities are not detected during postnatal period, urinary system anomalies are seen more frequently in cases of progression of pyelectasis. [1,4,5,8,9] In compliance with the literature, the 4 cases in present study where antenatal pyelectasis progressed, urinary system anomalies were found, and 3 cases underwent surgical intervention. Also in parallel with the literature, [1,4,8,9] pyelectasis was detected more frequently in male fetuses, and the 4 cases with urinary anomalies were of male gender.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…[1] While in most cases, urological abnormalities are not detected during postnatal period, urinary system anomalies are seen more frequently in cases of progression of pyelectasis. [1,4,5,8,9] In compliance with the literature, the 4 cases in present study where antenatal pyelectasis progressed, urinary system anomalies were found, and 3 cases underwent surgical intervention. Also in parallel with the literature, [1,4,8,9] pyelectasis was detected more frequently in male fetuses, and the 4 cases with urinary anomalies were of male gender.…”
Section: Discussionsupporting
confidence: 80%
“…[4,9] If pyelectasis persists through postnatal period, voiding cystourethrography, which is diagnostic for VUR and PUV, should be recommended. [4,8] In present study, VUR was detected in 2 (20%) cases, and PUV in 1. UPJ stenosis is one of the most frequently (9%) reported causes of antenatal pyelectasis, and is generally bilateral.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations